Hipertensión arterial en los pacientes hospitalizados en el área de clínica del hospital Julius Doepfner de la ciudad de Zamora, en el año 2014 - Carrión Ochoa, Mayra Fernanda (2015)
Hypertension is the increase in blood pressure chronically is a measurement of the force exerted against the walls of the arteries as the heart pumps blood through the body; it can cause many complications, if not treated in time. This research work, are intended to determine the prevalence of hypertension in patients hospitalized in the area hospital clinic Doepfner Julius, of the city of Zamora. For compliance, the following descriptive methodology, literature, cross fixed field arose: a survey was applied to 80 people, who were hospitalized, in which the following parameters were considered: sociodemographic characteristics, complications, family history, medical checks and blood pressure, use of antihypertensive medications, type of diet, physical activity, consumption of snuff and alcohol, likewise home visits were made hypertensive patients. With the data obtained, we proceeded to obtain the prevalence, which is 15.71%. Among the most important risk factors are, family history with 80%, the failure of medical checks and blood pressure in 45%, inadequate food type with 43.75%, lack physical activity to 36, 25%. Prior to the known during the course of the study, a training plan based on basic knowledge and preventive measures to raise awareness and change the lifestyle, thus achieving contribute to improve the life of hypertensive patients and family welfare executed , by which I conclude that hypertension is a health problem that affects most of the population in adulthood